THE ENVIRONMENTAL CRISIS AND BLINDNESS (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
This paper proposes a legal-social reflection based on the work of José Saramago, “Blindness”, drawing a parallel with the global environmental crisis, focusing on the challenges in the consolidation and effectiveness of the National Solid Waste Policy. The research aims to make possible ways of calling for citizenship and implementing the procedural arrangements proposed in the law, to remedy the current environmental crisis. As a resource to the importance of the dilemma about solid waste, the literary framework of the object of this brief study proposes reflections, leading to an understanding of the need for new attitudes to overcome the crisis, with significant changes in order to guarantee sustainability future generations. Based on the literary approach, a greater reflection is proposed on the consequences of indifference and lack of commitment to the National Solid Waste Policy. The methodology adopted is based on basic premises of the inductive method and is based on exploratory-bibliographic research, making use of books, articles, websites, magazines and scientific content from Congress proceedings, as well as analysis of the work in the literary and cinematographic version and some files in the area of ​​Law and Literature.